2006
DOI: 10.3892/or.15.2.369
|View full text |Cite
|
Sign up to set email alerts
|

The preserved expression of neuropilin (NRP) 1 contributes to a better prognosis in colon cancer

Abstract: Abstract. Vascular endothelial growth factor A (VEGF-A)plays an essential role in tumor progression through stromal neovascularization in malignant solid tumors. Neuropilin (NRP) is considered to be the specific receptor for limited types of VEGF-A isoform, VEGF165. The clinicopathological implications of NRP are not well understood in colon cancer, while almost all colon cancers overexpressed VEGF-A. We examined the expression levels of NRP1 and NRP2 genes in 54 colon cancer cases and paired extraneoplastic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
0
28
1
Order By: Relevance
“…These effects have been often explained by the role of Nrp1 in supporting VEGF signaling (17,19,20). In contrast to these findings, in other studies, an elevated expression of Nrp1 was associated with more favorable prognosis of patients with colon cancer (21) and reduced tumor growth in experimental models in mice (22); moreover, a VEGF/Nrp1-dependent pathway suppressing cell viability has been proposed in 1 specific case (23). These discrepancies are currently unresolved and they might reflect cell-specific responses and/or the involvement of different signaling pathways.…”
Section: Introductioncontrasting
confidence: 50%
“…These effects have been often explained by the role of Nrp1 in supporting VEGF signaling (17,19,20). In contrast to these findings, in other studies, an elevated expression of Nrp1 was associated with more favorable prognosis of patients with colon cancer (21) and reduced tumor growth in experimental models in mice (22); moreover, a VEGF/Nrp1-dependent pathway suppressing cell viability has been proposed in 1 specific case (23). These discrepancies are currently unresolved and they might reflect cell-specific responses and/or the involvement of different signaling pathways.…”
Section: Introductioncontrasting
confidence: 50%
“…Increased expression of Np-1 and Np-2 correlates with tumor aggressiveness, advanced disease stage, and poor prognosis (3941). In contrast, several studies have reported that Np-1 overexpression in tumor cells reduces motility and tumorigenicity or prolonged patient survival (4245). Possible reasons for discrepancies between various studies may include the expression of functional receptor/ligand repertoire (e.g., plexins) and/or the ratio of VEGF-A to SEMA3 within the particular tumor microenvironment.…”
Section: Discussionmentioning
confidence: 93%
“…5,[15][16][17] Although the prognostic impact of NRP-1 expression in AML was unknown so far, the prognostic value of NRP-1 expression in solid tumors has already been investigated by others. Preserved expression of NRP-1 contributes to a better prognosis in colon cancer, 18 whereas overexpression of NRP-1 correlates with poor prognosis in human glioma. 19 In non-smallcell lung cancer (NSCLC), co-expression of NRP-1 and NRP-2 is associated with poorer prognosis.…”
mentioning
confidence: 99%